Family environment and frequency of vegetable consumption among children aged 6 to 12 years - Raggio, Laura; Herrera, Guadalupe; Gámbaro, Adriana (Frontiers in Nutrition, 2025)
IntroductionDaily consumption of vegetables in recommended quantities is associated with health benefits. Its intake during the early years of life plays an essential role in the development of healthier eating habits. This study aims to contribute to the understanding of children’s eating behavior towards vegetables by exploring the frequency of consumption along with certain parental factors within the family environment of children between 6 and 12 years old.MethodsFactors such as nutritional knowledge (NK), frequency of vegetable consumption (FVC), interest in vegetable consumption, personal appreciation for vegetable consumption, and awareness of the health benefits associated with their consumption were examined.ResultsThe parental factors studied showed a positive correlation for some of the vegetables studied. Therefore, the necessity to study these factors individually rather than in groups is evident. Additionally, NK was found to influence the consumption of some of the vegetables studied.Discussion/ConclusionDespite being aware of the health benefits associated with its intake, parents with lower levels of NK were shown to have lower FVCs and a greater willingness to increase their consumption. Therefore, increasing the parents’ FVC is necessary to improve their children’s FVC.